2018
DOI: 10.3389/fpls.2018.00108
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an RNA-Seq Differential Gene Expression Analysis Depending on Biological Replicate Number and Library Size

Abstract: RNA-Seq is a widely used technology that allows an efficient genome-wide quantification of gene expressions for, for example, differential expression (DE) analysis. After a brief review of the main issues, methods and tools related to the DE analysis of RNA-Seq data, this article focuses on the impact of both the replicate number and library size in such analyses. While the main drawback of previous relevant studies is the lack of generality, we conducted both an analysis of a two-condition experiment (with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 68 publications
(76 reference statements)
4
59
1
Order By: Relevance
“…Since the first use of RNA-Seq to analyze transcriptomic data [ 42 ], we know more on the parameters necessary to optimize detection of differentially expressed genes. Lamarre et al recently showed that the read depth in part compensates for the number of replicates to increase the ratio of differentially expressed genes detected [ 43 ]: with 20 million reads (for 20,000 DE genes - corresponding to a coverage of 1000 reads per gene) and 2 replicates, 85% of DE genes are found, and 8 replicates are needed to reach a ratio of 100%, while with 2.5 million reads (~ coverage 125 reads/gene) and 2 replicates, only 15% of DE genes are detected and the use of 8 replicates increases the ratio of DE genes to only 60%. In our miR differential expression analysis, we performed only two biological replicates.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first use of RNA-Seq to analyze transcriptomic data [ 42 ], we know more on the parameters necessary to optimize detection of differentially expressed genes. Lamarre et al recently showed that the read depth in part compensates for the number of replicates to increase the ratio of differentially expressed genes detected [ 43 ]: with 20 million reads (for 20,000 DE genes - corresponding to a coverage of 1000 reads per gene) and 2 replicates, 85% of DE genes are found, and 8 replicates are needed to reach a ratio of 100%, while with 2.5 million reads (~ coverage 125 reads/gene) and 2 replicates, only 15% of DE genes are detected and the use of 8 replicates increases the ratio of DE genes to only 60%. In our miR differential expression analysis, we performed only two biological replicates.…”
Section: Discussionmentioning
confidence: 99%
“…Further, biological coefficient of variation (BCV) was calculated using the "estimateGLMCommonDisp" function. Finally, differential expression p-values were computed using the readCount files of the two treatments using the EdgeR "ExactTest" method (https://bioconductor.org/packages/release/bioc/html/edgeR.html) 88 which can handle data with small sample size 89 . The "ExactTest" method is the quantile-adjusted conditional maximum likelihood (qCML) method, which is applicable for single factor analysis.…”
Section: Molecular Characterization Rna Extraction Library Preparatmentioning
confidence: 99%
“…Twelve libraries were constructed using the TruSeq RNA Library Prep Kit (Illumina Inc.) and sequenced on an Illumina platform by Beijing Nuohe Zhiyuan Company. DEGs were analyzed using edgeR (version 3.8.6) with the exact test method described by Lamarre et al (2018). The versions of tomato reference genome and annotation database were SL2.50 and ITAG release 2.40 respectively.…”
Section: Rna-seq and Analysis Of The Differentially Expressed Genes (mentioning
confidence: 99%